The Protecting State in the Context of International Crises: Between Theory and Practice - عيسى مؤيد; نور الدين خازم; أحمد عمر (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Establish a system of protecting states to enable the conflicting parties to continue dialogue regarding the protection of their populations. The agreements stipulate, since the beginning of the conflict, the necessity for each party to appoint a protecting state to ensure the implementation of the agreements and additional protocols. The appointed delegates of the protecting states are subject to the approval of the parties to the conflict with whom they carry out their duties. The idea of our research is based on knowing the extent of the effectiveness of the role of the protecting state in implementing international humanitarian law. This research was addressed with definitions of the protecting state، an explanation of the parties that assume the responsibilities of the protecting state، we also explained the tasks and powers of the protecting state، and finally we presented applied cases of the role of the protecting state. In this research، we explained the nature of the protecting state in the first requirement، and we also explained the tasks and powers of the protecting state and its application cases in the second requirement. In order to achieve the desired goal of the establishment of the protecting state، we proposed separating the work of the aforementioned state from the initiative or acceptance of the conflicting parties. In other words، in more brief terms، we see granting the aforementioned state delegated powers to carry out its tasks as soon as there is a need to use its services.